Kaunda of Zambia - Temple, M. M.; Sokoni, John (London, Nelson, 1967)
A biography of the Northern Rhodesian who helped bring independence to his country, now called Zambia, and became its Prime Minister in 1964.
Keywords: Kaunda, Kenneth D. -- 1924- -- Juvenile literature; Kaunda, Kenneth D. -- 1924-